Dampak Kepercayaan Konsumen Terhadap Developer dalam Suksesnya Pelaksanaan Perjanjian Pengadaan Perumahan - Gina Hafizah; Rahma Sekar Putri Iswari; Icha Serlina; Marisa Yasmin; Fadhilla Dwi Octavia; Nadia Eldira; Amylia Sri Rahayu; Adrian Westito (CV. ITTC INDONESIA, 2023)
Indonesia is a developing country that continues to carry out development in all fields, both in the material and spiritual fields, where the development aims to realize the development goals of a just and prosperous society, one of the developments in the material sector includes facilities and infrastructure such as housing development both on a luxury scale, medium, even up to housing for the people (subsidized). While the nature of the research used in this writing is descriptive, namely by drawing conclusions from a general problem to the concrete problems at hand, then the existing legal material is analyzed to see if it can answer the problems raised by providing an overall picture